ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL ARITMATIKA SOSIAL BERDASARKAN TAHAPAN NEWMAN - Widya Ningsih; Euis Eti Rohaeti; Rippi Maya (IKIP Siliwangi, 2021)
Social arithmetics is a mathematical material which uses very close everyday life. For this reason, social arithmetics is very important to be understood properly in order to we can use maximal. In learning social arithmetics, students often experience mistakes when working on problems. This study aims to determine the mistakes students and their causes based on the Newman error analysis method. This study uses descriptive qualitative method. This research was held in MTs Negeri 1 Cimahi City by taking 30 students of grade VIII for the sample. The instruments in this study were 4 essay questions that have been tested for validity, reliability, distinguishing features, and difficulty indexes. The data in this study were processed using Microsoft Excel. After analyzing based on students' answers, the research shows that some of the students have a problem with Newman method. The most common type of error is the students can’t concluding the final answer (enconding errors). The other type of errors that students experience the least is reading errors.